A pilot study of transcutaneous sacral nerve stimulation for faecal incontinence. (November 2013) - Thomas, G. P.; Norton, C.; Nicholls, R. J.; Vaizey, C. J.
Abstract Aim Although effective in faecal incontinence (FI), sacral nerve stimulation (SNS) is expensive and requires two procedures. It carries a small risk of infection and electrode migration. Transcutaneous SNS is noninvasive and cheap. Two small studies have reported the results when applied to segments S3 but there is no information on its effectiveness when applied to the whole sacral area. Method A pilot study was carried out of self‐administered transcutaneous SNS given over a 4‐week period for 12 h a day. A 2‐week bowel diary was kept for the final 2 weeks and compared with baseline. Patients were assessed using the St Mark's Incontinence Score, a visual analogue scale assessing satisfaction with bowel habit, the Rockwood FI Quality of Life (QOL) score and SF‐36 QOL score. Results Of the 10 patients recruited, two achieved complete continence. There was a statistically significant reduction in the median (interquartile range) frequency of incontinent episodes per week from 9.5 (7.5) to 3 (7.38) (P = 0.03), and in the median frequency of defaecation per week from 25.5 (19.5) to 14.5 (14.9) (P = 0.007). There was a statistically significant improvement in the median ability to defer defaecation from 1 (1.25) to 4.5 (4.5) min (P = 0.02). There was also a statistically significant improvement in the St Marks Incontinence Score from 20 (5.25) to 14.5 (8.0) (P = 0.01) and in the bowel habit satisfaction visual analogue scale from 8.5 (20) to 45 (33) (P = 0.008). There was no change in the Rockwood FI QOL or SF‐36 QOL scores. No complications were reported. Conclusion Transcutaneous SNS appears to be an effective and safe treatment for FI. Larger controlled studies are needed to explore this further.